Obsessions and confessions of a book life - Franklin, Colin (Oak Knoll Press ; Books of Kells ; Bernard Quaritch, Ltd., 2012)
"An autobiographical narrative of the career of British author, bookseller, and book collector Colin Franklin, discussing his life and experiences in the book world. Includes essays on figures in the book trade who have influenced and fascinated Franklin. Illustrated in color and black and white"--